Correction: Epidermal Growth Factor Receptor in Prostate Cancer Derived Exosomes - Kharmate, Geetanjali; Hosseini-Beheshti, Elham; Caradec, Josselin; Chin, Mei Yieng; Tomlinson Guns, Emma S. (PloS one, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0154967.].